Dual‐polarised crossed‐dipole antenna with improved beamwidth. Issue 6 (26th February 2018) - Zhang, Zhi‐Ya; Zhao, Yarui; Wu, Dan; Zuo, Shao‐Li; Ji, Luyang; Yang, Xiao‐dong; Fu, Guang
Abstract : A wideband dual‐polarised crossed‐dipole antenna with improved beamwidth is investigated in this study. The proposed antenna consists of a pair of orthogonal placed crossed dipoles, which are fed by Marchand baluns through an electromagnetic coupling. Each dipole has two bent metal arms. By adding four simple parasitic elements on both sides of the crossed dipole, the beamwidth of the proposed antenna is significantly enhanced. The antenna is capable of realising two orthogonal linear polarisations when the two input ports are excited separately. A prototype of the proposed antenna is fabricated and measured. A measured port‐to‐port isolation of 28 dB and a stable radiation pattern at both the E ‐ and the H ‐plane are achieved, with the antenna gain in the range of 6.5 ± 0.6 dBi. In addition, the measured results show that the impedance bandwidth of the two ports is about 25% ranging from 403 to 518 MHz for voltage standing wave ratio <2. A good agreement is achieved between the simulated results and the measured ones.